PENGARUH KINERJA LINGKUNGAN DAN KEPEMILIKAN PUBLIK TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018 – 2022 - Gusti Ayu Putu Wulan Rahmasari; Dian Ayu Rahmadani (Nusantara Hasana Journal, 2024)
This research examines the influence of environmental performance and public ownership on corporate social responsibility (CSR) disclosure using mining companies listed on the Indonesia Stock Exchange (IDX) and also registered in the Environmental Performance Rating Program (PROPER). The sample collection method in this study employs purposive sampling, with 43 samples meeting the research criteria during the period 2018-2022. The available data is then processed using multiple regression analysis techniques. The research results, as indicated by the T-test values, show significant findings, demonstrating that environmental performance has an impact on CSR disclosure. Significant results are also obtained for the public ownership variable, indicating that this variable influences CSR disclosure.